Conceits of democracy in democratic and nondemocratic countries - Zagrabina, Anna. (International Political Science Review)
Democratic experience constitutes an essential part of people$1 (Bs world view and affects their understanding of democracy. This statement is confirmed by evidence from the World Values Survey (WVS) showing that the concept of democracy among citizens differs in democratic and nondemocratic societies. Democratic citizens associate democracy principally with gender equality, while people in nondemocratic countries associate it more strongly with a prospering economy and social control. People in democratic countries are also less likely to associate democracy with army rule and the intervention of religious authorities in political life than people in nondemocratic countries.- Reproduced s
Keywords: Democratic experience, Mass attitudes, Gender equality, Visible and invisible attributes of democracy, Democracy as habitat